2016
DOI: 10.7554/elife.19662
|View full text |Cite
|
Sign up to set email alerts
|

Actin is an evolutionarily-conserved damage-associated molecular pattern that signals tissue injury in Drosophila melanogaster

Abstract: Damage-associated molecular patterns (DAMPs) are molecules released by dead cells that trigger sterile inflammation and, in vertebrates, adaptive immunity. Actin is a DAMP detected in mammals by the receptor, DNGR-1, expressed by dendritic cells (DCs). DNGR-1 is phosphorylated by Src-family kinases and recruits the tyrosine kinase Syk to promote DC cross-presentation of dead cell-associated antigens. Here we report that actin is also a DAMP in invertebrates that lack DCs and adaptive immunity. Administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 96 publications
4
48
0
Order By: Relevance
“…One might therefore anticipate that extracellular actin sensing preceded the evolution of adaptive immunity and constitutes an ancient mechanism for detecting tissue injury, with its roots perhaps in tissue repair. Consistent with that notion, actin injection into Drosophila melanogaster induces sterile JAK/STAT responses akin to ones previously seen in the context of injury or stress (Srinivasan et al , ). Interestingly, although there is no DNGR‐1 in Drosophila , the response requires the fly orthologues of Src and Syk arguing for possible evolutionary conservation of the pathway of extracellular actin detection (Srinivasan et al , ).…”
Section: Detecting Damagesupporting
confidence: 72%
“…One might therefore anticipate that extracellular actin sensing preceded the evolution of adaptive immunity and constitutes an ancient mechanism for detecting tissue injury, with its roots perhaps in tissue repair. Consistent with that notion, actin injection into Drosophila melanogaster induces sterile JAK/STAT responses akin to ones previously seen in the context of injury or stress (Srinivasan et al , ). Interestingly, although there is no DNGR‐1 in Drosophila , the response requires the fly orthologues of Src and Syk arguing for possible evolutionary conservation of the pathway of extracellular actin detection (Srinivasan et al , ).…”
Section: Detecting Damagesupporting
confidence: 72%
“…In contrast, there is strong evidence of direct involvement of actin in invertebrate innate immunity. In Drosophila, extracellular actin triggers a response associated with wounding and dead cell clearance (Srinivasan et al, 2016). Actin-derived antimicrobial peptides have been identified in A. rubens (Maltseva et al, 2007), and extracellular actin has been shown to mediate antimicrobial defense in the mosquito Anopheles gambiae (Sandiford et al, 2015).…”
Section: Actin-binding Proteinsmentioning
confidence: 99%
“…Actin exists in a balance between monomeric and filamentous forms, and acts as a damage‐associated molecular pattern. Circulating actin was detected in patients with severe burns for up to 28 days after injury.…”
Section: Discussionmentioning
confidence: 99%